DETERMINAN INDEKS SAHAM SYARIAH INDONESIA - Ayif fathurrahman; Rahma Aprilia Widiastuti (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2021)
This study was conducted to determine and analyze the effect of inflation, exchange rates, and the BI Rate on the Indonesian Sharia Stock Index (ISSI). The method used in this research is the Error Correction Model (ECM). The data used are 55time series. Based on the analysis that has been done, the research results show that in the short term only the BI Rate has a significant negative effect on the Indonesian Sharia Stock Index (ISSI). Meanwhile, in the long term, the Exchange Rate and BI Rate variables have a significant negative effect on the Indonesian Sharia Stock Index (ISSI). Variable inflation has no effect on the Indonesian Sharia Stock Index (ISSI).